DNA barcodes and ethnomedicinal use of Sharpnose guitarfish Glaucostegus granulatus by the locals at Keylong, Lahaul and Spiti, Himachal Pradesh. Issue 1 (2nd January 2020) - Singh, Ashutosh; Jabin, Gul; Joshi, Bheem Dutt; Thakur, Mukesh; Sharma, Lalit Kumar; Chandra, Kailash
Abstract: Illegal trade of fishes is common and has been in practice since ages for the support of livelihood and as dietary supplements. However, several species are protected in the Wildlife (Protection) Act, 1972 of India and their trade is restricted under CITES. In this article, we report trade of Sharpnose guitarfish ( Glaucostegus granulatus) for the ethnomedicinal remedy, identified using DNA barcoding in the Keylong district of Lahaul and Spiti, Himachal Pradesh. This study provides the first DNA barcode of Sharpnose guitarfish. In order to handle wildlife offense cases we emphasize that a large reference database for other fishes in trade is needed.